2017
DOI: 10.1080/08870446.2017.1387261
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the effects of a decision intervention on mammography intentions: The roles of worry, fear and perceived susceptibility to breast cancer

Abstract: The results provide insight into the mechanism of action of the intervention by showing that PSBC mediated the effects of the intervention on mammography intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…As posited by the theory of planned behavior, 8 we found that both lower level of screening intention and a decrease in screening intention were associated with lower rates of screening after 18 mo. Previous literature examining the relationship between screening intention and behavior only did so in the context of increasing screening adoption [2][3][4][5][6][7] ; our results adds to the literature by showing that in the context of screening cessation, intention is also a strong predictor of behavior. These findings have several important implications.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As posited by the theory of planned behavior, 8 we found that both lower level of screening intention and a decrease in screening intention were associated with lower rates of screening after 18 mo. Previous literature examining the relationship between screening intention and behavior only did so in the context of increasing screening adoption [2][3][4][5][6][7] ; our results adds to the literature by showing that in the context of screening cessation, intention is also a strong predictor of behavior. These findings have several important implications.…”
Section: Discussionsupporting
confidence: 56%
“…1 Not surprisingly, numerous studies have aimed at promoting the adoption of breast cancer screening. [2][3][4][5][6][7] Based on the theory of planned behavior, which posits that intention is the most important and proximal predictor of behavior, 8 studies have found a moderate association between breast cancer screening intention and receipt of screening, 2,3 and a number of interventions have targeted screening intention as the outcome. [4][5][6][7] All of these studies focused on increasing screening rates.…”
mentioning
confidence: 99%
“…First, First choice treatment regimen and plan and Auxiliary treatment regimen and plan tended to reflect more specialized information for patients; therefore, they were merged and modified to form Treatment regimen and plan . Second, the statement “ survival time ” in Survival time and prognosis after treatment could have somewhat sinister connotations and cause the patients to feel anxious about how long they would live after being diagnosed . Therefore, the item was revised to Therapeutic effects and prognosis to shift patients' attention to treatment effectiveness, rather than survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Eight negative relationships between anticipatory anxiety constructs and breast cancer screening intention ( n = 2) and behaviour ( n = 6) were identified within the studies reviewed 26,68–72 . In three of these relationships, it was not clear what the anticipatory anxiety pertained to.…”
Section: Resultsmentioning
confidence: 99%